Penerapan Media Video Tutorial Pada Kompetensi Dasar Penataan Sanggul Top Style Kelas XI Di SMKN 3 Kediri - Novikasari Jati Permata; Nia Kusstianti; Maspiyah; Biyan Yesi Wilujeng (Program Studi Pendidikan Tata Rias, 2025)
The method of conveying information in an interesting and easy-to-understand way is using video tutorials. The level of effectiveness of video tutorials in conveying basic skills of top style bun arrangement as teaching materials in class XI of SMK Negeri 3 Kediri, student learning achievement after using video tutorial media on top style bun material, student responses to the use of video tutorials on learning skills of top style bun material as a learning aid. This study applies a quantitative approach. To collect information, an observation sheet is used to assess the quality of video tutorial media, cognitive and psychomotor tests are applied to evaluate student learning achievement, while questionnaires are used as a means of obtaining the required information. Video tutorials that discuss top style bun arrangement material are suitable media to be used and introduced to students as a learning tool. The average achievement is very satisfactory, with material components of 80%, media 90%, and language 85%. Students from grade XI showed achievement of scores above the KKM standard that has been set at SMK Negeri 3 Kediri, which is set at 75. Their learning achievement on the use of video learning media in top style bun arrangement lessons reached an average of 97 and 100% completion. Student responses to learning media lessons in the form of video tutorials in the learning process showed quite high effectiveness, with an achievement level reaching 83.8%. Keywords: Video tutorial media, top-style bun styling.